AKUNTANSI PENJUALAN BAHAN KEBUTUHAN POKOK DI SWALAYAN CV.BERKAT ANUGERAHBARONG TONGKOK - DAMAYANTI ,Elfreda Aplonia Lau, Titin Ruliana, DAMAYANTI , Elfreda Aplonia Lau, (EKONOMIA, 2016)
The purpose and usefulness are expected from this study as follows:To know the amount of sales obtained in Supermarkets CV. Berkat Anugerah Barong Tongkok in 2013 and 2014. To know the amount of net income earned in Supermarkets CV. Berkat Anugerah Barong Tongkok in 2013 and 2014. Based on the background described above, the main problem of this study is as follows: "Is the gross profit in 2014 at the supermarket CV. Berkat Anugerah Barong Tongkok higher than 2013?Â The analytical instrument used in this study is total revenue and net income by making daily notes on financial income and expenses of the business that is being run or recapitulation. The daily notes better known as cash flow,Based on the analysis and discussion of the results obtained:Sales in 2013 got a significant increase whereas in 2014 has decreased. Cost of goods sold in 2013 decreased compared to 2014 an increase in sales of merchandise on the CV. Berkat Anugerah. Depreciation in 2013 and 2014 is equal. Especially in buildings and equipment depreciation of CV. Berkat Anugerah. For the operational costs incurred Supermarkets CV. Berkat Anugerah in 2014 bigger than 2013. Based on analysis result showed gross profit earned during 2014 has decreased from the year 2013, so the hypothesis is rejected.Â